Century‐long stomatal density record of the nitrophyte, Rubus spectabilis L., from the Pacific Northwest indicates no effect of changing atmospheric carbon dioxide but a strong response to nutrient subsidy. Issue 24 (1st December 2021) - Ydenberg, Ron; Leyland, Ben; Hipfner, Mark; Prins, Herbert H. T.
Abstract: Triangle Island on Canada's Pacific coast is home to a large, globally important seabird breeding colony. The shrub Salmonberry Rubus spectabilis and tussock‐forming Tufted Hairgrass Deschampsia cespitosa together form ~70% of vegetation coverage and contain the vast majority (~90%) of seabird nesting burrows. Salmonberry has in recent decades greatly expanded its coverage, while that of Tufted Hairgrass has receded. Seabirds prefer not to burrow under Salmonberry, making its ongoing expansion a potential conservation issue. We investigated three hypotheses proposed to explain Salmonberry's expansion (climate change, biopedturbation, and nutrient input), using comparisons of stomatal density of Salmonberry leaves sampled from Triangle Island, other seabird colonies, other coastal locations, and from historical specimens in herbaria. Stomatal density helps regulate photosynthetic gain and control water loss, and responds to light, nutrient, carbon dioxide, and water availability. Differing patterns of stomatal density are expected among sample locations depending on which of the hypothesized factors most strongly affects Salmonberry's performance. Our data are most consistent with the nutrient input hypothesis. We discuss possible reasons why Salmonberry has expanded so recently, even though Triangle has been a large seabird colony for at least a century and likely much longer. Abstract : Measures of stomatal density made in leaves of the shrub Salmonberry Rubus spectabilis at sites along coastal British Columbia support the hypothesis that nutrient input from the large seabird colony is driving its expansion on Triangle Island. Previous papers on this issue identified "climate change" and "biopedturbation" as the causes. The approach is novel and provides another way to assess vegetation changes on seabird islands.